Influenza Vaccine-Induced Antibody Responses Are Not Impaired by Frailty in the Community-Dwelling Elderly With Natural Influenza Exposure - Narang, Vipin; Lu, Yanxia; Tan, Crystal; Camous, Xavier F. N.; Nyunt, Shwe Zin; Carre, Christophe; Mok, Esther Wing Hei; Wong, Glenn; Maurer-Stroh, Sebastian; Abel, Brian; Burdin, Nicolas; Poidinger, Michael; et al. (Frontiers in Immunology, 2018)
BACKGROUND Elderly adults over 65 years of age are recommended to receive seasonal influenza vaccination as they are at a higher risk of infection and its complications than the younger community. The elderly are often stratified according to frailty status where frail individuals are more susceptible to adverse health outcomes than their non-frail counterparts, however, it is not known whether immunity induced by influenza vaccination is impaired in the frail elderly. STUDY DESIGN 205 elderly subjects of Chinese ethnicity in Singapore (mean age 73.3 ± 5.3 years, 128 females and 77 males) were administered the recommended trivalent inactivated 2013-14 seasonal influenza vaccine (Vaxigrip) containing A/H1N1, A/H3N2 and B strains. The elderly subjects were stratified into three groups according to Fried’s frailty criteria (59 frail, 85 pre-frail, 61 robust) and were also ranked by Rockwood’s frailty index (RFI). Statistical associations were evaluated between frailty status and pre- and post-vaccination antibody titres in sera measured by Hemagglutination inhibition (HAI) and microneutralization (MN) assays. Immunological responses across frailty strata were also studied in terms of leukocyte cellular distribution, cytokine levels and gene expression. RESULTS Post-vaccination, 83.4% of the subjects seroconverted for A/H1N1, 80.5% for A/H3N2, and 81% for the B strain. The seroconversion rates were comparable across frailty groups (A/H1N1, ANOVA, p = 0.7910; A/H3N2, ANOVA, p = 0.8356, B, ANOVA, p = 0.9741). Geometric mean titres of HAI and MN as well as seroprotection rates were also similar in all three frailty groups and uncorrelated with RFI (Spearman, r = 0.023, p = 0.738). No statistically significant differences were observed between the frailty groups in vaccine-induced modulation of leukocyte populations, cytokine responses and gene expression profiles of peripheral blood mononuclear cells (PBMCs). Whereas, pre-vaccination HAI titres due to natural exposure and post-vaccination titres were positively correlated. CONCLUSION The majority of the elderly subjects seroconverted for seasonal influenza upon vaccination, and importantly, influenza vaccination-induced humoral immune responses and seroprotection were similar across the frailty strata, indicating that frail individuals may also benefit from influenza vaccination. Pre-existing antibodies due to natural exposure appeared to positively influence vaccine-induced antibody responses.